Solution:

324000000

= 324 × 10^{6}

= 3.24 × 10^{2}× 10^{6}

= 3.24 × 10^{2+6}

= 3.24 × 10^{8}

Solution:

45000000

= 45×10^{6}

= 4.5×10^{1}×10^{6}

= 4.5×10^{1+6}

= 4.5×10^{7}

Solution:

45

= 4.5×10

= 4.5×10^{1}

Solution:

101000

=1.01×100000

=1.01×10^{5}

Solution:

0.00671

= \(\frac{6.71}{100000}\)

= \(\frac{6.71×100}{10^5}\)

= 6.71×10^{2-5}

=6.71×10^{-3}

Solution:

0.0000435

= \(\frac{0.0000435×10000000}{10000000}\)

= \(\frac{435}{10^7}\)

Solution:

0.0000435

= \(\frac{0.0000435×10000000}{10000000}\)

= \(\frac{435}{10^7}\)

Solution:

= 2.4×10^{5}

= 240000

Solution:

= 3.2×10^{4}+2.3×10^{4}

= (3.2+2.3)×10^{4}

= 5.5×10^{4}

Solution:

299792458

= 2.99792458 × 100000000

= 2.99792458 × 10^{8} m/s

Solution:

3.2 × 10^{4} + 2.3 × 10^{4}

= ( 3.2 + 2.3 )× 10^{4}

= 5.5× 10^{4}

Solution:

5.7× 10^{1}×^{-4-1}

= 57× 10^{-4-1}

= 57× 10^{-5}

= \(\frac{57}{10^5}\)

= \(\frac{57}{100000}\)

= 0.00057

Solution:

2.6×1000 + 3.4×100

=2600 +340

= 2940

= 294×10^{1}

= 2.94×10^{2}×10^{1}

= 2.94× 10^{3}

Solution:

8.3×100 - 2.4×100

= 830-240

= 590

= 59×10^{1}

= 5.9×10^{2}

Solution:

72,000,000,000,000,000,000,000 kg.

= 72 × 10^{18}kg

= 7.2×10^{1}×10^{18} kg

= 7.2×10^{19} kg

Solution:

9.70 × 10^{6} + 8.3× 10^{5}

= 9.70× 10^{6} + 0.83× 10^{6}

= (9.70 + 0.83)× 10^{6}

= 10.53×10^{6}

= \(\frac{10.53}{10}\)× 10× 10^{6}

= 1.053×10^{1+6}

= 1.053×10^{7}

Solution:

1.2× 10^{5}

= \(\frac{1.2}{10}\) × 10× 10^{5}

= 0.12× 10^{6}

Now,

( 1.2× 10^{5}) + (5.35× 10^{6} )

= ( 0.12× 10^{6}) + (5.35× 10^{6})

= (0.12 + 5.35)× 10^{6}

= 5.47× 10^{6}

Solution:

7.00× 10^{-6}

= \(\frac{7.00}{10}\)× 10^{1}×10^{-6}

= 0.70× 10^{1-6}

= 0.70× 10^{-5}

Now,

8.41× 10^{-5} - 0.70× 10^{-5}

= 8.41× 10^{-5} - 0.70× 10^{-5}

= (8.41 - 0.70)× 10^{-5}

= 7.71× 10^{-5}

Solution:

\(\frac{1.20× 10^{-8}}{3.0×10^{-3}}\)

= \(\frac{1.20}{3}\)\(\times\)10^{-8 + 3}

= 0.40\(\times\)10^{-5}

= \(\frac{40}{100}\)\(\times\) 10^{-5}

= \(\frac {4.0 \times 10^1 \times 10^{-5}}{10^2}\)

=\(\frac{4.0\times10^{1-5}}{10^2}\)

= 4.0 \(\times\)10^{-4-2}

= 4.0\(\times\)10^{-6}

Solution:

2.4× 10^{-3}

= \(\frac{2.4}{10}\)× 10× 10^{-3} = 0.24× 10^{-2}

Now,

6.91× 10^{-2} + 0.24× 10^{-3}

= 6.91× 10^{-2} + 0.24× 10^{-2}

=(6.91 + 0.24 )× 10^{-2}

= 7.15× 10^{-2}

Solution:

4.9 \(\times\)10^{4}

= \(\frac{4.9}{10}\)\(\times\)10^{1}\(\times\)10^{4}

= 0.49 \(\times\)10^{1+4}

= 0.49\(\times\)10^{5}

Now,

1.33\(\times\)10^{5} - 4.9 \(\times\)10^{4}

= 1.33 \(\times\)10^{5} - 0.49\(\times\)10^{5}

= (1.33 - 0.49) \(\times\)10^{5}

= 0.84 \(\times\)10^{5}

= \(\frac{8.4}{10}\)\(\times\)10^{5}

= 8.4\(\times\)10^{4}